Effect of Priming Treatment to Enhance Seed Quality of Sorghum - NISHA; SS JAKHAR; AXAY BHUKER; SATPAL (Seed Research, 2026)
With a view to find out the effect of priming on germination and seedling vigour on sorghum (Sorghum bicolor L.) seeds, experiments were conducted during Kharif 2018 in Seed Technology Laboratory, Department of Seed Science & Technology, CCS Haryana Agricultural University, Hisar (Haryana), India.The seed of two forage sorghum variety (HC 136 and HJ 541) were evaluated under five priming treatments viz. T1: Untreated (control), T2: Hydration -dehydration (6 h,T3:Hydration – dehydration (6 h) + 0.25 % thiram treatment.T4: Hydration with GA3 (50 ppm for 6 h),T5:Hydration with sodium molybdate (500 ppm for 6 h) in complete randomized block design and replicated thrice.Maximum germination percentage and seedling length were observed when seeds primed withT4:Hydration with GA3 (50 ppm for 6 h), followed by Hydration – dehydration + 0.25 % Thiram treatment (T3)similar trend was also observed in all parameters. Among the treatments T1 Untreated (control) recorded minimum germination %, Seedling Length, seedling dry weight, Seed Vigour index and dehydrogenase activity. Among all the priming treatments T4 Hydration with GA3 (50 ppm for 6 h) was found to be the best priming treatment. Moreover, priming treatments have more pronounced effect on HJ541 maintained highest quality parameters followed than HC136 of sorghum seeds.